2015
DOI: 10.1007/s10620-015-3804-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Colitis Immunotherapy Targets Bin1 and Improves Colon Cell Barrier Function

Abstract: Our results suggest that a therapy based on Bin1 monoclonal antibody supporting mucosal barrier function and protecting integrity of the lymphoid follicle could offer a novel strategy to treat UC and possibly limit risks of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…Based on the study we recently demonstrated that treatment of experimental colitis with Bin1 monoclonal antibody would support mucosal barrier function by inducing the expression of TJ proteins thereby protecting the integrity of the lymphoid follicle. The therapy may be a novel strategy to treat UC and possibly limit risks of colorectal cancer (344). Thus lowering Bin1 levels may be a strategy that would lead to enhanced TJ proteins that, in turn, protects against pathogenic microorganisms from crossing the epithelial cells.…”
Section: Microbiome Effects On Intestinal Barrier Function and Inflammentioning
confidence: 99%
“…Based on the study we recently demonstrated that treatment of experimental colitis with Bin1 monoclonal antibody would support mucosal barrier function by inducing the expression of TJ proteins thereby protecting the integrity of the lymphoid follicle. The therapy may be a novel strategy to treat UC and possibly limit risks of colorectal cancer (344). Thus lowering Bin1 levels may be a strategy that would lead to enhanced TJ proteins that, in turn, protects against pathogenic microorganisms from crossing the epithelial cells.…”
Section: Microbiome Effects On Intestinal Barrier Function and Inflammentioning
confidence: 99%
“…BIN1 was initially identified in 1996 as a tumor suppressor; subsequently, however, additional functions have been attributed to different protein transcripts. Bin1 is a conserved member of the BAR (Bin‐Amphiphysin‐Rvs) family of adapter proteins implicated in diverse cellular processes including endocytosis, actin organization, programmed cell death, stress responses, and transcriptional control . The BIN1 gene has recently been identified as the most important risk locus for late‐onset Alzheimer's disease, after apolipoprotein E …”
Section: Introductionmentioning
confidence: 99%
“…Under the action of noxious stimulation, the barrier function of intestinal tract could be comprised and lead to disruption of normal physiology. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%